Odpowiedzi

2009-12-08T16:48:12+01:00
Napisz w najprostszej postaci i oblicz .

dla b = -1/3

(3b+4)-(2-3b)= 3b+4-2+3b= 6b+2

6b+2= 6× (-⅓) + 2= -2+2= 0


dla a = -3
3(2-a)+a(4-2a)=6-3a+4a-2a²= a-2a²+6

a-2a²+6 = -3-2 × (-3)² + 6= -3 -2×9+6 = -3-18+6= -15



dla a = - 1/5 ,
(4a-3)-(2-a)a = 4a-3 -2a+a² = 2a+a²-3

2a+a²-3= 2 × (-1/5) + (-1/5)² - 3 = -2/5+ 1/25-3 = -10/25+ 1/25-3= -9/25-3= -3 9/25

proszę;]
2009-12-08T16:51:32+01:00
(3b + 4) - (2-3b) = 3b + 4 -2+3b = 6b +2 (6 * 1/3) + 2 = -1

(2-a)+a(4-2a)= 6 - 3a + 4a - 2a (potęga)2 =
6 + a - 2a (potęga) 2 =
6-3-36 = -33

(4a-3)-(2-a)a = 4a - 3 - 2a + a (potęga)2 =
2a - 3 + a(potęga) 2 =
0.4 - 3 + 0.04 = - 2.56